Short-term PM1 exposure and sleep duration: a nationwide study using consumer-grade wearable devices - Jiajun Liu; Mintao Su; Junxiong Ma; Qinfeng Zhou; Hanxu Shi; Yujie Shi; Shuyu Huang; Yuchuan Tang; Peining Zhou; Kunyao Yu; Rui Su; Rui Zhou; et al. (Environmental Research Communications)
Insufficient sleep is a growing global health concern, linked to various adverse health outcomes. While the effects of PM _2.5 on health are well-documented, the impact of PM _1 exposure, particularly its interaction effects with temperature on sleep quality, remains less understood. This nationwide study included 1,100,294 records from 4,783 individuals nationwide using wearable devices to collect sleep data across China. Daily PM _1 exposure levels were derived from the China High Air Pollutants (CHAP) dataset, and hourly nighttime temperatures were obtained from the ERA5-Land dataset. Associations between PM _1 exposure and sleep duration were evaluated using linear mixed-effect models. An interquartile range (IQR) increase in PM _1 concentration significantly altered sleep duration: total sleep increased by 1.51 min (95% CI: 0.52 to 2.50), light sleep increased by 2.87 min (95% CI: 1.97 to 3.76), and deep sleep decreased by 1.28 min (95% CI: −1.81 to −0.75). Nighttime temperatures were negatively associated with sleep duration. High nighttime temperatures amplified the adverse impact of PM _1 on deep sleep reduction, while slightly mitigating its effect on light sleep. Stronger associations were observed in individuals aged 45 years and older, those with lower BMI, urban residents, and daily smokers. Although individual sleep duration changes appear modest, the cumulative impact of PM _1 on sleep structure, especially in vulnerable populations, poses significant public health risks in physiological restoration. Our research emphasizes the urgency of integrating nighttime temperatures and PM _1 emissions monitoring into strategies, particularly safeguarding sleep quality in vulnerable populations, including older adults, individuals with lower BMI, urban dwellers, and smokers.